2020
DOI: 10.25073/2588-1094/vnuees.4522
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Urban Transportation Infrastructure Development Projects on Residential Land Price in Cau Giay District, Hanoi City

Abstract: Urban transportation infrastructure development projects usually act as a lever for real estate values. This research aims to assess the effects of some projects on urban land prices in three wards of Cau Giay District, namely Quan Hoa, Dich Vong, and Dich Vong Hau wards. With 161 samples surveyed, we established a multivariate linear regression model initially having 11 variables. As the result, six variables are identified as having significant effect on land prices in the study area. Among those, three vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Rewari et al (2020) have highlighted that the connectivity between different businesses and the trade routes can only be developed with better transportation arras and creating the activities that can be effective for carrying out the trade in the countries. As referred to in the study of Thuy et al (2020) the different means of transportation can be used by businesses to create growth opportunities and create measures for better trade and portability in the countries. It has been observed that one of the major routes that are generally used for transportation is the ocean routes that the firms can use in different countries for dealing with the supply chain activities based on the assessment of Gray (2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Rewari et al (2020) have highlighted that the connectivity between different businesses and the trade routes can only be developed with better transportation arras and creating the activities that can be effective for carrying out the trade in the countries. As referred to in the study of Thuy et al (2020) the different means of transportation can be used by businesses to create growth opportunities and create measures for better trade and portability in the countries. It has been observed that one of the major routes that are generally used for transportation is the ocean routes that the firms can use in different countries for dealing with the supply chain activities based on the assessment of Gray (2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this regard, According to Rewari et al [ 34 ], different enterprises and trade channels may be connected by developing activities that are efficient for carrying out smooth trade across countries and trade routes. At another instance, a study by Thuy et al [ 39 ] revealed that businesses may leverage various modes of transportation in order to develop expansion possibilities and implement initiatives to improve trade and portability in their countries. Also, Gray [ 5 ] confirmed that often, utilized transportation routes are employed by companies to deal with supply chain operations.…”
Section: Literature Reviewmentioning
confidence: 99%